KONDISI SOSIAL EKONOMI DAN PERSEPSI MASYARAKAT PEMBUKA LAHAN DI KAWASAN CAGAR ALAM DUSUN BESAR KOTA BENGKULU. - Deselina, Daselina; Purwoko, Agus; Fajri, M. (Jurnal AGRISEP, 2004)
Dusun Besar is located in town area of Bengkulu. Dusun Besar preserve area has multi functions, i.e. as a natural habitat of Orchid Pencil (Vanda Hookeriana),  and as an area of relocation  of freshwater (reservoir),  and water diffusion area. The aim of this research  was to analyze condition  of economic social  and perception  society  about preserving  of Dusun  Besar  behavior  in farm clearing.  Second investigating  relation  between  social  economic  condition and perception  eagar  Alam  Dusun  Besar with its behavior  in opening  of farm in Dusun Besar.  The research  was conducted  in Dusun Besar Orchard  area. Amount  of responder  were  15 % from total  population  farm in Preserve Area. Data analysis  use  qualitative  and  quantitative  analysis.  Earnings  of responder  have  real relation  to its behavior in farm cleaning in Dusun Besar. While education level, family responsibility,  and perception of respondent  do not correlate to behavior in farm in Preserve Area. Socio economic determinants